Timing noise of 133 pulsars in the southern hemisphere - N. Namkham (2020)
© Published under licence by IOP Publishing Ltd. Pulsars are small, dense stars which rotate up to 1500 times per second and emit radio waves in a directed beam along their magnetic axis. Pulsars are remarkably stable rotators, and by measuring the arrival times of the radio beam the pulsar can be used as a clock in space. Applications of pulsar timing have led to the first exoplanet system, stringent tests of theories of gravity and have the potential to detect gravitational waves. Yet, the pulsars spin is not perfect, and understanding the imperfections (timing noise) is important to the aforementioned applications. Here, we present the analyses of timing noise of 133 pulsars observed with the Parkes radio telescope in Australia over the period of 4 years. The results show that as consistent with pulsar toy model equations the measured breaking index, representing the magnitude of timing noise, has an anti-correlation with the spin-down rate, spin-down energy and characteristics magnetic fields, and it also has a positive correlation with the characteristics age at significant of 10σ. The error in the slope values of those relationships are in the order of 9 percent, which may imply imperfections of the pulsar toy model.